2001
DOI: 10.1002/1097-0010(200102)81:3<295::aid-jsfa811>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Free amino acid composition in primary and secondary inflorescences of 11 broccoli (Brassica oleracea var italica) cultivars and its variation between growing seasons

Abstract: Eleven broccoli cultivars were grown in the ®eld in spring/summer (April±July) and summer/ winter (September±January). Free amino acid composition was determined by HPLC in primary and secondary in¯orescences separately. A total of 17 amino acids were identi®ed: L-valine (Val). The major amino acid was L-glutamine, which represented on average between 39.5% (in cvs Durango and Green Valiant) and 55.5% (in cv Shogun) of the total amino acid content among cultivars, followed by L-glutamic acid with a variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…(2000) observed that the leaves contain more amino acids than the stems. Gomes & Rosa (2000) and Oliveira et al. (2008) showed that the distribution of amino acids is not similar in internal and external leaves in Brassica spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2000) observed that the leaves contain more amino acids than the stems. Gomes & Rosa (2000) and Oliveira et al. (2008) showed that the distribution of amino acids is not similar in internal and external leaves in Brassica spp.…”
Section: Resultsmentioning
confidence: 99%
“…These differences could be in part because of various factors such as genotype, environmental factors, growing conditions, maturity and part of the plant analysed (Kmiecik et al. , 1999; Gomes & Rosa, 2000; Ishida et al. , 2000; Lisiewska et al.…”
Section: Resultsmentioning
confidence: 99%
“…. F. rubripes had the highest ratio of TUAA/TAA among the three pufferfish, which indicated that the living environment, such as salinity, might affect the nutritional composition of farmed pufferfish, including flavor (Gomes and Rosa, 2000), while it has been suggested that free amino acids may influence fish flavor (Hwang and Chen, 2000). The influence of amino acid composition on flavor and variations in amino acid profile caused for example by varying rearing temperatures upon final product quality clearly represents an area deserved of future research (Gonzá lez et al, 2006).…”
Section: Amino Acidmentioning
confidence: 94%
“…Extraction was performed by sequential extraction with first 70% and then 90% v/v methanol in combination with a heating plate and a homogeniser [1,7]. After each extraction, the samples were centrifuged.…”
Section: Extraction and Hplc Analysis Of Free Amino Acidsmentioning
confidence: 99%
“…Free amino acids are implicated in secondary plant metabolism and in the production of compounds which directly or indirectly play an important role in the plant-environment interaction and in human health [1]. Additionally, amino acids directly contribute to the flavour and colour of food induced during thermal reactions in the stages of production, processing and storage of food [2].…”
Section: Introductionmentioning
confidence: 99%